Fraud Diamond: Four Elements of Financial Report Fraud Detection – Study on Coal Producers - Karmelia Agatha Made; Diyah Sukanti Cahyaningsih; Waluyo Djati (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2023)
The aim of this research is to examine the impact of fraud diamonds on the identification of fraudulent financial statements. Fraud diamonds, a framework used to detect fraudulent financial statements, considers various factors such as pressure (measured by ROA), opportunity (measured by Ineffective monitoring (IND)), rationalization (measured by auditor turnover (AUDCHANGE)), and capability (measured by the change of directors (DIRCHANGE)). The research sample comprised of 9 companies selected through purposive sampling. Logistic regression analysis was employed as the analytical method, with rationalization and capability serving as the independent variables, assessed through a binary variable with values 0 and 1. The findings indicate that pressure significantly influences the detection of fraudulent financial statements. Specifically, higher ROA values correspond to a lower likelihood of fraudulent financial statements. Opportunity also has an impact on the detection of fraudulent financial statements, as an increase in ineffective monitoring levels leads to a higher detection rate of financial statement fraud. On the other hand, rationalization does not affect the identification of fraudulent financial statements, suggesting that auditor turnover rate does not play a role in detection. Similarly, capability, represented by the replacement of the board of directors, does not impact the detection of fraudulent financial statements in companies.